Reverse Logistics of Electronic Waste in Brazil and in The World:: The Challenge of Dismantling the Actors - Sant’Anna, Lindsay Teixeira; Machado, Rosa Teresa Moreira; Brito, Mozar José de (Sustainability in Debate, 2015)
In order to review the literature about the national and international practices of the reverse logistics of electronics, so they can become lessons and contributions to the Brazilian scene, the authors of this article analyse the realities of Switzerland, a pioneer country in waste electrical and electronic equipment management (WEEE), The article also examines four other major generators of electronic waste: the United States of America, China, India and Brazil. Results point to a lack of articulation of actors in the reverse chain of WEEE in almost all the studied countries, while it identifies some explicit collaborative trials and the importance of adopting new partnerships that facilitate logistics. Successful WEEE reverse logistics depend on the State compliance at all levels of the Brazilian Federation, the involvement of the business sector, and partnerships with public research institutions and civil society organizations. Only this articulation will make reverse logistics of WEEE become a reality, capable of generating closed-loop production and electronics disposal mechanisms.